THE INFLUENCE OF SOCIAL MEDIA PROMOTION AND SERVICE QUALITY REGARDING PURCHASING DECISIONS AT FITTARA COFFEE SIDOARJO - Nurjanah Fitri Hastuti; Ayun Maduwinarti; Ni Made Ida Pratiwi (International Journal of Artificial Intelligence for Digital Marketing, 2024)
Currently, in the culinary industry this has happened. Companies now see greater business opportunities through the use of internet media as a promotional tool. With increasingly advanced technology, the internet is no longer a strange thing in product marketing. The company always pays attention to product quality, consumer needs, packaging and effective promotions. Many business promotions are now turning to social media because the majority of internet users in Indonesia are active in the trade and services sectors. Marketing strategies via social media can increase sales without large costs. Consumers also find it easier to get information about the products they want through technology which is part of e-commerce, which is the way companies communicate, promote and sell products via the internet. In Indonesia, in this globalization era, business competition is getting tighter with ongoing technological developments. The aim of conducting this line research is to find out whether knowledge of Promotion, Social Media, Service Quality influences Purchase Decisions at Fittara Coffee Sidoarjo. This type of research uses quantitative methods. The population is all buyers who have made transactions at Fittara Coffee Sidoarjo with a sample size of 100 respondents from distributing questionnaire statements via Google Form. The results obtained state that Social Media Promotion and Service Quality simultaneously have a positive and significant effect on purchasing decisions at Fittara Coffee Sidoarjo. Testing this hypothesis concluded partially that Social Media Promotion had a positive and significant influence on Purchasing Decisions, and Service Quality had a positive and significant influence on Purchasing Decisions.